Product logo identity design: a case study on increasing the value of micro, small, and medium enterprises (MSMEs) snack products - Ekawardhani, Yully Ambarsih; Fasya, Muhammad Na'imulloh Ismina; Nasruddin, Merlina Fatimah (Gelar: Jurnal Seni Budaya, 2024)
A cohesive identity for MSME products is imperative, particularly in light of the prevalence of similar types and shapes of products, especially snacks. The adoption of an identity in the form of a logo has the potential to serve as a differentiating factor for snack products. This research aims to devise an identity design for the product logo of Micro, Small, and Medium Enterprises (MSMEs) potato chip snacks. To this end, the art-based research (ABR) method was employed as a facilitator to understand creative ideas in a visual work. The research method comprised two stages: the initial stage involved observing and communicating with relevant individuals to understand the challenges faced by the product. The subsequent stage entailed the implementation of the design thinking method to gain an understanding of design centered on human needs. The previous logo was found to be inconsistent and lacked legibility. MSME snack products must contend with competition in the market, particularly to enhance recognition among similar products. The result is a logo identity design that aligns with the values of the product owner. Adopting this new logo identity design differentiates the snack food product from competing products while concurrently reinforcing its image.